Towards anti-fingerprint sol-gel coatings - Ngian, Sie Khee. (2010)
With the arising of touch screen technology, the demand for anti-fingerprint coating on the screen of electronic devices elevated drastically. However, there is no standard test method in fingerprint adhering property quantification. Hence, a new test method in anti-fingerprint characterization is proposed in this study. An artificial fingerprint (AF) liquid is suggested to be used as testing liquid in contact angle measurement. Besides, human mark deposition simulation is also made using AF liquid with incorporation of small amount of inorganic solid filler. From these two approaches, the anti-fingerprint property of a surface is able to be defined in quantitatively and qualitatively manner. Therefore, the recipes for artificial fingerprint (AF) liquid and artificial finger mark are suggested in this study. In the second part of this study, a good resistant of fingerprint adhering coating is synthesized via sol-gel process with proper combination of surface chemistry modification and surface roughening. The influence of surface morphology on fingerprint adhering property is studied and discussed using Wenzel and Cassie-Baxter Model.